LONG-TERM DEBT FINANCING AND OPERATING PERFORMANCE OF LISTED INDUSTRIAL GOODS FIRMS IN NIGERIA (Journal of Global Accounting, 2025)
The study examined the effect of long-term debt financing on the operating performance of listed industrial goods firms in Nigeria. The specific objective was to ascertain the effect of long-term debt to equity ratio and long-term debt to asset ratio on the operating cashflow margin of listed industrial goods firms in Nigeria. Ex-post facto research design was used in the study. Thirteen listed industrial goods firms made up the population of the study from which a sample size of nine was selected using purposive sampling technique. Secondary data were sourced from the annual reports of the firms for thirteen, spanning 2012-2024. Test of hypotheses was carried out using panel estimated generalised least squares, which revealed that long-term debt to equity ratio has a significant and negative effect on operating cashflow margin of listed industrial goods firms in Nigeria (β = –0.043294, p = 0.0433); long-term debt to asset ratio has a positive and significant effect on operating cashflow margin of listed industrial goods firms in Nigeria (β = 0.283497, p = 0.0051). In conclusion, firms able to channel long-term borrowings into asset-backed investments or productive resources are more likely to generate sufficient cash flows to cover their operational needs. The study recommends that financial managers of listed industrial goods firms in Nigeria should reduce excessive reliance on long-term debt relative to equity as maintaining a balanced debt–equity mix will help prevent the erosion of operating cash flow margins caused by high debt servicing obligations, thereby improving the firm’s ability to fund day-to-day operations without undue strain.
Keywords: Long-Term Debt Financing; Long-Term Debt to Asset Ratio; Long-Term Debt to Equity Ratio; Operating Performance